Systematic literature review: leveraging data deduplication strategies & hashing techniques to eliminate data redundancy in cloud environments - M. A., Fazlina; Latip, Rohaya; Ibrahim, Hamidah; Abdullah, Azizol (World Academy of Research in Science and Engineering, 2019)
Technology advancements are core contributors to massive data evolutions across the globe. As data is blooming universally the storage and network bandwidth are on high demands. Many survey evidences that data for in storage seems to have multiple same or similar copies of data and to be exact very minimal of the total data are unique where else, the remaining amount are identical data shared between numerous users. This scenario resulting high bandwidth and storage consumptions,especially for cloud providers. Variety of solutions has anticipated enhancing cloud storage performance. This Systematic Literature Review (SLR) is focusing on Deduplication in Cloud Replication Environment and the results are alleviated to show holistic deduplication adoption and adaption in cloud environments. The study successfully addressed four (4) research questions and analysis was done for future research.